Immune responses in mildly versus critically ill COVID-19 patients - Nasrollahi, Hamid; Talepoor, Atefe Ghamar; Saleh, Zahra; Eshkevar Vakili, Mahsa; Heydarinezhad, Paria; Karami, Narges; Noroozi, Maryam; Meri, Seppo; Kalantar, Kurosh (Frontiers in Immunology, 2023)
The current coronavirus pandemic (COVID-19), caused by SARS-CoV-2, has had devastating effects on the global health and economic system. The cellular and molecular mediators of both the innate and adaptive immune systems are critical in controlling SARS-CoV-2 infections. However, dysregulated inflammatory responses and imbalanced adaptive immunity may contribute to tissue destruction and pathogenesis of the disease. Important mechanisms in severe forms of COVID-19 include overproduction of inflammatory cytokines, impairment of type I IFN response, overactivation of neutrophils and macrophages, decreased frequencies of DC cells, NK cells, and ILCs, complement activation, lymphopenia, Th1, and Treg hypoactivation, Th2 and Th17 hyperactivation, as well as decreased clonal diversity and dysregulated B lymphocyte function. Given the relationship between disease severity and an imbalanced immune system, scientists have been led to manipulate the immune system as a therapeutic approach. For example, an-ti-cytokine, cell, and IVIG therapies have received attention in the treatment of severe COVID-19. In this review, the role of immunity in the development and progression of COVID-19 is discussed, focusing on molecular and cellular aspects of the immune system in mild vs. severe forms of the disease. Moreover, some immune-based therapeutic approaches to COVID-19 are being investigated. Understanding key processes involved in the disease progression is critical in devel-oping therapeutic agents and optimizing related strategies. Expert Opinion: The identification and investigation of cellular and molecular cascades during different phases of mild vs. severe forms of disease may provide us a better understanding of the mechanisms involved in improper immune responses during COVID-19 and might help us prevent the transition from mild to severe stages of COVID-19.